Contagious Anxiety: Anxious European Americans Can Transmit Their Physiological Reactivity to African Americans. (December 2017) - West, Tessa V.; Koslov, Katrina; Page-Gould, Elizabeth; Major, Brenda; Mendes, Wendy Berry
During interracial encounters, well-intentioned European Americans sometimes engage in subtle displays of anxiety, which can be interpreted as signs of racial bias by African American partners. In the present research, same-race and cross-race stranger dyads ( N = 123) engaged in getting-acquainted tasks, during which measures of sympathetic nervous system responses (preejection period, PEP) and heart rate variability were continuously collected. PEP scores showed that African American partners had stronger physiological linkage to European American partners who evidenced greater anxiety—greater cortisol reactivity, behavioral tension, and self-reported discomfort—which suggests greater physiological responsiveness to momentary changes in partners' affective states when those partners were anxious. European Americans showed physiological linkage to African American and European American partners, but linkage did not vary as a function of their partner's anxiety. Using physiological linkage offers a novel approach to understanding how affective responses unfold during dynamic intergroup interactions.